Procedure of trade service division and an analysis of automation opportunities in Prime Bank Limited - Shashi, Farhana Rahman (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.